Disclosure Determinants of Hazardous Toxic Waste in Indonesia - V Wiratna Sujarweni; Djoko Suhardjanto; Setianingtyas Honggowati; Sri Hartoko (Green Publisher Indonesia, 2022)
This study aims to examine the effect of Suppliers, Consumers, community, Shareholders, and Employees on Hazardous Toxic Waste Disclosures in Indonesia by compiling its index. This study uses primary and secondary data. The primary data were obtained by distributing the Hazardous Toxic Waste Disclosure questionnaire to academics, environmental service officials, suppliers, consumers, local communities, shareholders, and company employees. Meanwhile, the secondary data were obtained from the annual reports of manufacturing companies, Management of Mineral, Gas, and Coal Mining, as well as hospitals listed on the Indonesia Stock Exchange (IDX) between 2012-2019. A purposive sampling technique was used, and the independent variables include Suppliers, Consumers, Community, Shareholders, and Employees controlled by Company Size, and Profitability, while the dependent variable is Hazardous Toxic Waste Disclosure. The data were processed using the descriptive test and multiple linear regression. The Stakeholder Theory was used to solve the problem of low Hazardous Toxic Waste Disclosure in Indonesia. The results showed 21 items of the Hazardous Toxic Waste Disclosure index. In a previous study, Suppliers, Consumers, Communities, and employees positively affected Hazardous Toxic Waste Disclosures. Meanwhile, shareholders had a negative effect on the dependent variables